Distinct neural signatures of schizotypy and psychopathy during visual word‐nonword recognition. Issue 12 (18th April 2022) - Vanova, Martina; Aldridge‐Waddon, Luke; Norbury, Ray; Jennings, Ben; Puzzo, Ignazio; Kumari, Veena
Abstract: Previous behavioural data indicate lower word‐nonword recognition accuracy in association with a high level of positive schizotypy, psychopathy, or motor impulsivity traits, each with some unique contribution, in the general population. This study aimed to examine the neural underpinnings of these associations using functional magnetic resonance imaging (fMRI) in a volunteer sample. Twenty‐two healthy English‐speaking adults completed self‐report measures of schizotypy (Oxford‐Liverpool Inventory of Feelings and Experiences [O‐LIFE]), psychopathy (Triarchic Psychopathy Measure [TriPM]), and impulsivity (Barratt Impulsiveness Scale [BIS‐11]) and underwent whole‐brain fMRI while performing a lexical decision task (LDT) featuring high and low‐frequency words, real nonwords, and pseudohomophones. Higher positive schizotypy (Unusual Experiences) was associated with lower cerebellum activity during identification of low‐frequency words (over real nonwords). Higher Boldness (fearless dominance) and Meanness (callous aggression) facets of psychopathy were associated with lower striatal and posterior cingulate activity when identifying nonwords over words. Higher Motor Impulsivity was associated with lower activity in the fusiform (bilaterally), inferior frontal (right‐sided), and temporal gyri (bilaterally) across all stimuli‐types over resting baseline. Positive schizotypy, psychopathy, and impulsivity traits influence word‐nonword recognition through distinct neurocognitive mechanisms. Positive schizotypy and psychopathy appear to influence LDT performance through brain areas that play only a supportive (cerebellum) or indirect role in reading‐related skills. The negative association between Motor Impulsivity and activations typically found for phonological processing and automatic word identification indicates a reduced bilateral integration of the meaning and sound of mental word representations, and inability to select the appropriate outputs, in impulsive individuals. Abstract : Positive schizotypy and Motor Impulsivity influence word‐nonword recognition through distinct neurocognitive mechanisms. Higher Motor Impulsivity was associated with lower activity in brain areas typically involved in phonological processing and automatic word identification, namely the fusiform gyrus bilaterally, right inferior frontal gyrus, and temporal gyri bilaterally, during word‐nonword recognition. Positive schizotypy was associated with activity modulation in the cerebellum, which is considered to play a supportive role in phonological and semantic processing.